Analisis Pemenuhan Kebutuhan dan Penyelesaian Kelangkaan Sumber Daya Air (Studi Kasus Kelurahan Tlogowaru, Malang) - M. Tamim Syaifullah; Asfi Manzilati (Jurnal Ilmu Ekonomi dan Pembangunan, 2015)
The purpose of this study was to evaluate the water supply system. And give people the knowledge to be able to manage a clean water source either by private or by together. This study is expected to be informed about how the fulfillment of Water Resources and how the fulfillment of water resources and how to overcome shortages for residents in the Village Tlogowaru, Kedungkandang subdistrict, Malang. And for the Government / PAM / village to allocate water resources for the community or residents who experience water scarcity. This research uses descriptive method. Selection of this approach because the concept of water treatment is not easy to be identified and measured in quantity and absolute. The results showed that the water scarcity in the region Tlogowaru that is located in Malang is actually a natural thing. Scarcity of water resources is influenced by the geography. On the other hand, Hipam is one of the few sources of clean water used by residents Tlogowaru. Hipam is the only source of water available in the Village Tlogowaru. However, the role is still considered to be less effective in addressing the water scarcity in the Village Tlogowaru. Keywords: water resources, clean water, hipamJEL Classification: P47, Q01